Bipolar Disorder and Child Custody in Indonesian Religious Courts: Operationalizing Sadd al-Dharī‘ah to Balance Child Welfare and Parental Rights - Syaifuddin Zuhdi; Lutfi Robiatul Adawiyah; Marisa Kurnianingsih; M Junaidi; Abdul Hakim (Faculty of Sharia, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
As mental health disorders have received more attention from modern-day legal systems, questions about the impact of such disorders in relation to child custody proceedings become increasingly pertinent. One of the controversial questions pertains to whether bipolar disorder may be regarded as a valid reason to restrict or transfer custody rights from one parent to another. This study discusses the legal status of bipolar disorder within cases of child custody litigation before Indonesian Religious Courts and formulates an Islamic legal framework to examine custody cases involving psychosocially disabled parents. Qualitative doctrinal legal research is used as the methodology of the study, and statutory, conceptual, case, and comparative approaches are employed. The findings reveal that there is no reason for bipolar disorder to be automatically considered as an obstacle to child custody. It must be noted that the significance of such a disorder lies in its impact on the ability of parent to provide adequate care to their children as well as posing risks to the welfare of children. To solve this problem, this study operationalizes sadd al-dharī‘ah into four phases of judicial evaluation: taḥqīq al-manāṭ (verification of facts), taqdīr al-mafsadah (risk evaluation), takyīf ḥukmī (classification of the risk into legal terms), and tadbīr muwāzan (balance between the risks and benefits). Thus, this framework allows for conducting evaluations of child custody cases based on rational criteria and at the same time protecting the interests of children. In this way, the this study argues that custody restrictions may only be imposed if there is proof that bipolar disorder poses risks to the safety or health of the child.